Review of animal health services in India - Singh, Rajendra; Birthal, Pratap Singh; Rathore, B S (The Indian Journal of Animal Sciences, 2012)
There has been substantial growth in animal health services in India. The number of veterinary livestock units per veterinary institution has declined from 9451 in 1984-85 to 7325 in 1992-93. During the periods the number of veterinary hospitals, polyclinics and dispensaries increased by 26% and the number of veterinary aid centres increased by 23%. Similarly, there has been a substantial increase in manpower engaged in animal health services. The number of veterinary livestock units per veterinarian declined from 23935 in 1971 to 9359 in 1993, An overwhelming majority of veterinarians is engaged in government sector. However, the number of private practitioners has increased manifolds recently. The incidence and mortality rates due to various diseases have declined significantly and there has been substantial improvement in the productivity of livestock. Though animal health sector has expanded in terms of infrastructure and technical expertise, many of the veterinary institutions do not have adequate supplies of preventive and curative inputs because od shortage of funds. Adequate attention needs to be given since a majority of livestock owners in India are poor and cannot afford high cost of prevention and control of diseases. The future strategy should emphasize on adequate supplies of inputs for prevention and control of diseaes along with improvement in nutrition and management, as to realize the full productive potential of livestock.